A study on correlation between depression, fear of fall and quality of life in elderly individuals - Mishra, Neeti; Mishra, Anil Kumar; Bidija, Mansi (International Journal of Research in Medical Sciences, 2017)
Background: Fear of falling in elderly is a major cause of loss of independence, which has an effect on the physical function in elderly individuals. Depression is another important public health problem for older adults, because late life depression might have devastating consequences, such as an increase in mortality. QOL of older adults has become an important issue, because of demographic changes resulting from the ageing of the population. The goal of the study was to assess the depression and fear of fall which will provide further insights into the relationship between QOL, depression and fear of fall among elderly individuals in India. Methods: The sample consisted of 62 elderly people of age between 65 years to 75 years (mean=71.96, SD±5.92) were taken in the study. Depression was assessed using the 30-item geriatric depression scale (GDS), fear of falling was measured using falls efficacy scale (FES), QOL was assessed using the 26-item, World Health Organization Quality of Life, brief version (WHOQOL-BREF). Results: The data was analysed using Pearson co-efficient of correlation to examine the relationship between GDS, FES, and WHOQOL-BREF. The correlation co-efficient between GDS and FES was 0.5257 (p<0.05) and correlation coefficient between GDS and WHOQOL was 0.4372 (p<0.05). Conclusions: This study concluded that there was a significant association between the depression, fall efficacy, and QOL in the elderly people. This relationship has an important implication for the development of the rehabilitation programs that aim to improve the balance confidence and motivation will diminish its impact on QOL in elderly people.